Prácticas inclusivas en la educación indígena, el caso de una escuela primaria en Ensenada, Baja California, México - Solis del Moral, Sharon Stephanie; Tinajero Villavicencio, María Guadalupe; Cárdenas, Juan Páez (Universidad de Costa Rica, 2023)
More than three decades ago, several countries undertook the commitment to develop inclusive education systems based on the postulates of "Education for All", promoted by international organizations. Mexico was no exception, and although its policies have been gradual, the construction of inclusive schools has become a central issue, which is a challenge, especially for indigenous schools located in marginalized contexts. From an interpretive paradigm and a qualitative approach, an ethnographic case study was conducted with the objective of collectively constructing the inclusive practices promoted by the 8 people who make up the teaching staff of an indigenous school in Ensenada, Baja California, Mexico, to document and understand them in their daily lives. For this purpose, two ethnographic techniques were used, the teacher interview and on-site observation in the school and in the classrooms; data were collected during eight months, (August 2019 to March 2020). Through the qualitative content analysis technique, it was identified that the teaching staff develops inclusive practices demarcated by their possibilities of action, which acquire meaning in their context. The findings refer to actions such as preventing absenteeism and ensuring permanence, especially for students at risk of social exclusion; attention to students with disabilities and/or specific educational needs; and adaptations in the school trajectory. In the classrooms, teachers make curricular adjustments and adjustments in their classes according to their individual, group, economic and health characteristics. The conclusions highlight how the practices are considered as inclusive as they respond to the characteristics and needs of the context in which the students are located.